OBSERVATIONS ON THE PLANKTON ECOLOGY OF PULICAT LAKE - Kaliyamurthy, M (Indian Journal of Fisheries, 2011)
Observations made on the spatial, temporal and tidal variations of the plankton of Pulicat Lake during April 1968 to March 1970 indicated that the plankton was rich in quantity and quality at stations nearer to the mouth than at the upper reaches. The primary peak of the phytoplankton occurred during May-July and that of the zooplankton in April-May. A close similarity was noticed in the characteristics of plankton between the lake and the coastal waters of Madras. A marked seasonal cycle in the phytoplankton production related to ttdal leases was observed, especially during summer and postmonsoon seasons. The zooplankton populations varied more with the time of the day than with the tide. Phytoplankton showed some direct relationship, while zooplankton and settling volume of plankton had no such relationship with the salinity conditions. The zooplankton appeared to have direct correlation with water temperature, but the latter had no apparent effect on i^ytoplankton. Zoi^lankton production of the southern sector of the lake was 1.4 to 2 times higher than that of the northern sector, which, was reflected in the fish yield of the respective zones.